Assessoria jurídica popular - teoria e prática emancipatória - Maia, Christianny Diógenes (2006)
This dissertation searched to analyze the Legal Service Organizations – LSO, an up-to-date and emancipatory legal movement, which has as main objective the promotion and effectivess human rights of the sectors excluded socially, economically, politically or culturally and, therefore, the consolidation of a juster society for all. In this sense, the theoretical bases of the Movement were researched, mainly the Critical Legal Studies, the Alternative Law and the Post-positivism; and their assumptions, such as the Democratic State of Law, the ample access to justice, the Community Participatory Legal Pluralism, the Popular Education as a pedagogical approach to a emancipatory legal education and a Law as an instrument of social transformation. Furthermore, the characteristics of the Legal Service Organizations and their differences from Legal Aid were pointed out. A brief review of the LSO and some cearense experiences of this innovatory legal practice were also related in this work.